2018
DOI: 10.3892/ol.2018.9587
|View full text |Cite
|
Sign up to set email alerts
|

miR‑125a is upregulated in cancer stem‑like cells derived from TW01 and is responsible for maintaining stemness by inhibiting p53

Abstract: microRNA (miR)-125a and miR-125b were demonstrated to translationally and transcriptionally inhibit the mRNA level of p53 following the induction of chemo-reagents in our previous report. As a small subpopulation of nasopharyngeal carcinoma (NPC), cancer stem-like cells (CSCs) function critically in multi-malignant behaviors, including tumorigenesis and metastasis; however, the expression pattern and regulatory role of miR-125a, miR-125b and p53 in CSCs derived from NPC remain unclear. In order to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…These mechanistic experiments indicate that miR‐125a is a crucial regulator in inflammation and immune responses, which might explain the results in our study that miR‐125a plasma expression could predict sepsis risk, and was negatively correlated with severity and pro‐inflammatory cytokines levels in sepsis patients. In addition, there is a report showing that U6 might not be an appropriate internal reference for miRNAs detection; however, for circulating miR‐125a expression detection, there are still mounting studies using U6 as an internal reference …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanistic experiments indicate that miR‐125a is a crucial regulator in inflammation and immune responses, which might explain the results in our study that miR‐125a plasma expression could predict sepsis risk, and was negatively correlated with severity and pro‐inflammatory cytokines levels in sepsis patients. In addition, there is a report showing that U6 might not be an appropriate internal reference for miRNAs detection; however, for circulating miR‐125a expression detection, there are still mounting studies using U6 as an internal reference …”
Section: Discussionmentioning
confidence: 99%
“…Univariate and multivariate Cox's proportional hazards model analyses of factors affecting accumulating survival sepsis risk, and was negatively correlated with severity and pro-inflammatory cytokines levels in sepsis patients. In addition, there is a report showing that U6 might not be an appropriate internal reference for miRNAs detection; however, for circulating miR-125a expression detection, there are still mounting studies using U6 as an internal reference 12,[30][31][32].…”
mentioning
confidence: 99%
“…Therefore, even though there were no changes in GC cell proliferation, migratory and invasive ability in vitro , it is possible that miR-125a-5p functions as a tumor suppressor in vivo by regulating the tumor microenvironment, including effects on tumor angiogenesis. It is still possible that miR-125a-5p may regulate stemness (37), a critical feature of tumor formation, just like the tumor size. Therefore, in vivo experiments assessing the effect of miR-125a-5p on tumor growth and metastasis are required.…”
Section: Discussionmentioning
confidence: 99%
“…According to our analyses, we found that the identified genes are closely related to the cell cycle pathway. Several reports indicated that the upstream and downstream proteins of the cell cycle pathway are regulated by P53 ( Zhang et al, 2018 ; Chen et al, 2019 ; Wang et al, 2020 ). Within 24 h after treatment with 0.75 μmol/L podophyllotoxin, we observed the effect of podophyllotoxin on the mRNA level of identified genes in MD-MBA-231 and MD-MBA-468 cells.…”
Section: Resultsmentioning
confidence: 99%